Therapist competencies in the context of group-based exercise programs in medical rehabilitation: a qualitative study with patients and exercise therapists from Germany - André Arik Schuber; Madeleine Gernert; Andrea Schaller (BMC, 2023)
Abstract Background Group-based exercise programs account for nearly half of exercise therapy services provided in German medical rehabilitation facilities. However, information about necessary therapist competencies for the successful execution of these programs is sparse. Thus, the aim of this qualitative study was to explore relevant therapist competencies in the context of group-based exercise programs from the patients' and therapists' perspective. Methods Semi-structured interviews were conducted with five rehabilitation patients following a 3-week inpatient orthopedic rehabilitation program as well as five exercise therapists with work experience in group-based exercise therapy. Data were analyzed using structuring content analysis according to Kuckartz. Results From 155 topic-related text passages, collected over 10 interviews, four competency categories with 16 subcategories and respective characteristics were identified. In addition to professional expertise like biomedical knowledge, exercise therapists were expected to possess a multitude of didactic-methodological, personal, and social-communicative abilities. Conclusion Our results suggest that the psychosocial, behavioral and educational goals of group-based exercise programs necessitate a wide range of therapist competencies. These conform to the multidimensional nature of exercise therapy and should therefore be covered in vocational and continuing education.